Chalcone‐Benzotriazole Conjugates as New Potential Antimicrobial Agents: Design, Synthesis, Biological Evaluation and Synergism with Clinical Drugs. Issue 4 (8th March 2017) - Liu, Hanbo; Gopala, Lavanya; Avula, Srinivasa Rao; Jeyakkumar, Ponmani; Peng, Xinmei; Zhou, Chenghe; Geng, Rongxia
Abstract: A series of chalcone‐benzotriazole conjugates as new potential antimicrobial agents were synthesized and characterized by 1 H NMR, 13 C NMR, IR and HRMS spectra. Antimicrobial assay manifested that some target compounds gave moderate to good antibacterial and antifungal activities. The N ‐1 derived benzotriazole5e and N ‐2 derived benzotriazole6a exhibited valuable inhibitory efficacy against some tested strains. Especially, derivative6a gave superior antifungal efficacies against C. utilis, S. cerevisiae and A. flavus (MIC=0.01, 0.02, 0.02 µmol/mL, respectively) to Fluconazole. The drug combination of compound5e or6a with antibacterial Chloromycin, Norfloxacin and antifungal Fluconazole respectively showed stronger antimicrobial efficiency with less dosage and broader antimicrobial spectrum than their separated use alone. The preliminary interaction with calf thymus DNA revealed that compound6a could intercalate into DNA to form6a ‐DNA supramolecular complex which might be a factor to exert its powerful bioactivity. Molecular docking study indicated strong binding of compound6a with DNA gyrase. The structural parameters such as molecular orbital energy and molecular electrostatic potential of compound6a were also investigated, which provided better understanding for its good antimicrobial activity. Abstract : A new type of α ‐benzotriazolyl chalcones were synthesized and screened for their antimicrobial activities. Their synergistic effects with clinical drugs and interaction mechanism with DNA were investigated.